Different Diagnostic Procedure of Typhoid Fever: A Review Update (Journal of Current and Advance Medical Research, 2014)
Typhoid fever is diagnosed by using a combination of the clinical presentation, the isolation of Salmonella typhi from body fluids and by Widal test. In the first week of illness, the diagnosis may be more difficult because in this invasive stage with bacteraemia; the symptoms are those of generalized infections without localizing feature. Cultures of stool, urine, rose spots, bone marrow, gastric and intestinal secretions can all be useful for diagnosis. The efficacy of culture varies with the specimen being tested. In addition, the prehospital antibiotic therapy frequently used in developing countries complicates the isolation of infectious agents from clinical specimens especially from blood. Bone marrow appears to be the most suitable specimen because bone marrow culture has a higher sensitivity than blood culture. The methods of bacterial isolation are inherently slow and take more than 48 hours. That is why, serologic analysis becomes more important. The Widal test has got limitations such as the difficulty in interpretation, the need to demonstrate a fourfold rise after a week and necessity of knowing the endemicity of the area and is useful only in selected patients. The available methods of diagnosis of typhoid fever are either time consuming or are not absolutely reliable. An accurate diagnosis of typhoid at an early stage is important not only for an etiological diagnosis of the patient but also to identify individuals who may serve as a source of infection. The outer membrane protein on the surface of Gram negative bacteria has been considered as important antigens to induce host immune response. Enzyme-linked immunosorbent assays (ELISA) have been considered an alternative approach for the diagnosis of typhoid fever. Therefore, this present review has been designed to describe the different diagnostic procedure of typhoid fever.DOI: http://dx.doi.org/10.3329/jcamr.v1i2.20517 Journal of Current and Advance Medical Research Vol.1(2) 2014: 35-41